Sanita-Gizi: Program Pendampingan Sanitasi Lingkungan dan Perilaku Konsumsi Makanan Bergizi untuk Optimalisasi Tumbuh Kembang Anak Usia Sekolah - Yuliyanti Setiawati; Arlina Muhtar; A. Bida Purnamasari; Sulistiawaty Sulistiawaty (JKM: Jurnal Kemitraan Masyarakat, 2026)
Environmental sanitation and unhealthy dietary patterns can increase school-age children’s vulnerability to infection, micronutrient deficiencies, and excessive weight, ultimately affecting growth, development, and learning readiness. This community service program aimed to improve children’s knowledge and skills in environmental sanitation and balanced nutritious food consumption through SANITA-GIZI. The program was implemented at UPT SDN 179 INP Balang Desa Mangadu, Kecamatan Mangarabombang, Takalar Regency, involving 30 school-age children. An educational and participatory approach was applied through interactive learning, handwashing demonstrations, waste-sorting simulations, food-grouping games, balanced-plate practice, and teacher-assisted mentoring. Evaluation used pretest–posttest questionnaires, skill observation sheets, and participant response forms. Data show that the mean knowledge score increased from 58.3 to 86.7, equivalent to a 28.4-point improvement and an N-gain of 0.68 (moderate category). Correct handwashing practice increased from 26.7% to 90.0%, while the ability to arrange a balanced nutritious plate increased from 23.3% to 86.7%. The program received a very positive response from 93.3% of participants. SANITA-GIZI may serve as a simple, contextual, and replicable school education model. Nevertheless, claims concerning growth and developmental optimization require sustained mentoring and longer-term anthropometric and dietary-behavior assessments.